THE ROLE OF MODERN TEACHING METHODS IN LANGUAGE EDUCATION - Mamanazarova Rayhona Nurbek qizi, (TADQIQOTLAR, 2025)
Abstract In  the  21 st   century,  language  teaching  has  shifted  from  teacher-centered instruction  to  learner-centered  approaches  that  emphasize  communication, collaboration, and creativity. The process of globalization, the growth of international communication, and the widespread use of technology have significantly influenced the  way  languages  are  taught  and  learned.  Traditional  approaches,  such  as  the Grammar-Translation Method or the Audio-Lingual Method, which focused primarily on rote memorization and grammatical accuracy, are no longer sufficient to meet the communicative  needs  of  modern  learners.  Today,  education  systems  emphasize interaction, creativity, and learner autonomy as the foundation of effective language learning.  Modern  teaching  methods  in  language  education  aim  to  create  a  learner-centered environment where students actively participate in the learning process rather than passively receive information.